2023
DOI: 10.1002/anie.202216739
|View full text |Cite
|
Sign up to set email alerts
|

Second Sphere Effects Promote Formic Acid Dehydrogenation by a Single‐Atom Gold Catalyst Supported on Amino‐Substituted Graphdiyne

Abstract: Regulating the second sphere of homogeneous molecular catalysts is a common and effective method to boost their catalytic activities, while the second sphere effects have rarely been investigated for heterogeneous single‐atom catalysts primarily due to the synthetic challenge for installing functional groups in their second spheres. Benefiting from the well‐defined and readily tailorable structure of graphdiyne (GDY), an Au single‐atom catalyst on amino‐substituted GDY is constructed, where the amino group is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…158 Liu et al reported the Au SAs anchored on amino-substituted graphdiyne for efficient formic acid dehydrogenation (Figure 17m−n). 159 After 5 h of catalyst reaction by Au/GDY-NH 2 , the conversion of formic acid could reach over 99% (Figure 17o). Mao and co-workers fabricated the selective electrocatalysis by interfacing redox-active methylene green and graphdiyne.…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…158 Liu et al reported the Au SAs anchored on amino-substituted graphdiyne for efficient formic acid dehydrogenation (Figure 17m−n). 159 After 5 h of catalyst reaction by Au/GDY-NH 2 , the conversion of formic acid could reach over 99% (Figure 17o). Mao and co-workers fabricated the selective electrocatalysis by interfacing redox-active methylene green and graphdiyne.…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
“…(o) Dehydrogenation of formic acid with different catalysts. Reproduced with permission from ref . Copyright 2023, Wiley-VCH.…”
Section: Graphdiyne-based Catalytic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the unique incomplete charge transfer between GDY and metal atoms could increase the number and the stability of the active site. [15][16][17][18] Benetting from these superiorities, GDY has shown excellent performances and attracted greatly increasing interest from the elds of electrocatalysis, [19][20][21][22][23][24][25][26][27][28] photocatalysis, [29][30][31] energy conversion, [32][33][34][35][36][37] etc. [38][39][40] In this study, the highly active and stable OER, HER, as well as OWS were achieved on the heterostructure of FeOOH@GDY with electronic-donating and withdrawing interface structures, resulting in innite active sites which guarantee excellent catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the unique incomplete charge transfer between GDY and metal atoms could increase the number and the stability of the active site. 15–18 Benefitting from these superiorities, GDY has shown excellent performances and attracted greatly increasing interest from the fields of electrocatalysis, 19–28 photocatalysis, 29–31 energy conversion, 32–37 etc . 38–40…”
Section: Introductionmentioning
confidence: 99%